Evading terror? Terror Attacks and Internal Migration in Israel - Johanna von Borstel; Tom Gobien; Duncan Roth (European Regional Science Association (ERSA), 2014)
This paper empirically analyses the relationship between terror incidents and internal migration in Israel. Using a newly created database of region-to-region migration flows for the years 1998-2012, the empirical model regresses the annual flow of migrants from an origin subdistrict to a destination subdistrict on measures of terror incidents in the origin and the destination, respectively. The results indicate that terror in the destination subdistrict acts as a deterrent to migration into that region, whereas we find no evidence in support of the hypothesis that terror brings about outmigration.
Keywords: D74; J61; 330